Invention of a computer "Kyiv" architecture using a concept of Addressed Programming Language - Yuschenko, Yu.O. (Інститут програмних систем НАН України, 2022)
The article is devoted to the history of the origin of high-level programming in Ukraine. The transition from calculations by arithmometers and logarithmic rulers to solving problems on the computer "Kyiv" using pointers and tree-like formats (abstract data types are analogous) is described. The factors that contributed to this transition include: the experience of providing instructions for calculations by arithmometers, and the experience of programming on MESM. As a result a computer "Kyiv" has been developed with a hardware-implemented possibility of high-level programming, invention of the Addressed Programming Language with indirect addressing (pointers), tree formats and declarative capabilities.Hardware-realized demining of pointers in the computer "Kyiv" is one of the outstanding inventions of Ukrainian engineers and mathematicians at the initial stage of the information technologies development. At that time it was significantly ahead of the world technologies. Programming in computer "Kyiv", unlike Plankalkül, could identify and process complex structures. The paper describes the individual applications of the Address Programming Language, which was implemented on many Soviet-made computers and has been used by programmers for more than 20 years. Due to the so-called "Iron Curtain", scientists in the field of programming outside the post-socialist world still do not know about the invention of pointers by Kiev scientists. A textbook describing the Addressed Programming Language was translated into many languages. A monograph with a description of the computer architecture "Kyiv" and of the Addressed Programming Language was translated into English and published in the United States in 1966.Prombles in programming 2021; 4: 103-118